Eucalyptus globulus and Cymbopogon flexuosus essential oils antimicrobial and conservative effects against Salmonella enterica serovar typhimurium and possible cytotoxicity: an in vitro and in situ investigation in inoculated pork sirloin - Cleiton Jesus Andrade Pereira; Vithor Parada Garcia; Vitória Rose de Andrade; Milena Mattes Cerveira; Jéssica Silveira Vitoria; David de Andrade Cabral; Eliezer Avila Gandra; Janice Luehring Giongo; Rodrigo de Almeida Vaucher (Brazilian Journal of Microbiology, 2026)
Foodborne illnesses, particularly those caused by Salmonella spp., represent a major global health concern, with S. typhimurium being a significant contributor to outbreaks. The persistence of S. typhimurium in food production environments and its resistance to conventional disinfectants highlight the need for alternative antimicrobial solutions. Essential oils (EOs) from Eucalyptus globulus (EGEO) and Cymbopogon flexuosus (CFEO) have shown antimicrobial potential against S. typhimurium , but their mechanisms of action and cytotoxic effects on eukaryotic cells require further investigation to assess their safety for food applications, particularly in situ. We evaluated cytotoxicity in erythrocytes and zebrafish liver (ZF-L) cells using hemolysis (HA), MTT, and NR uptake assays. Additionally, we investigated the antimicrobial behavior of EGEO and CFEO against S. typhimurium ATCC 14,028 through MIC/MBC tests, time-kill assays, and a newly designed TSI-adapted test to assess the EOs’ impact on bacterial metabolism. An in situ experiment was also conducted to evaluate the preservative effects of EGEO and CFEO on pork sirloin contaminated with an infectious dose of S. typhimurium and treated with EO-based brines for 7 days under refrigeration. We monitored the presence of Salmonella spp., as well as pH, calcium (Ca²⁺), and magnesium (Mg²⁺) concentrations in the brined samples. Results indicated that CFEO was hemolytic above 0.73 mg/mL and EGEO above 0.45 mg/mL. The MTT assay showed that CFEO did not impair mitochondrial function from 2.941 mg/mL and EGEO from 14.36 mg/mL. NR uptake assay showed that both EOs did not impaired lysossomal function in ZF-L. The MICs and MBCs for CFEO and EGEO were 0.37 mg/mL and 1.79 mg/mL, respectively. Time-kill assays revealed bactericidal effects for CFEO at 4x and 2x MIC within 6 h, while EGEO showed a bactericidal effect only at 4x MIC. The EO-TSI agar assay demonstrated that EGEO inhibited sugar fermentation and sulfur metabolism, while CFEO impacted peptone oxidation and protein metabolism. In situ analyses showed CFEO caused more significant changes in color and odor of the pork samples than EGEO, while both maintained pH levels around 6. Ca²⁺ and Mg²⁺ levels were lower in CFEO-treated samples. Microbiological data confirmed the absence of Salmonella spp. in all samples except for two in the CFEO-brine group. None of the samples showed signs of autolysis or putrefaction, suggesting that both CFEO and EGEO, particularly EGEO, are feasible alternatives as food preservatives, depending on the desired application.